Addressing medical students' health challenges: codesign and pilot testing of the Preventive Remediation for Optimal MEdical StudentS (PROMESS) program - Angèle Métais; Léa Besnard; Bérénice Valero; Amélie Henry; Anne-Marie Schott; Gilles Rode; Julie Haesebaert; Jean-Baptiste Fassier; Sophie Schlatter (BMC Medical Education)
Abstract Background Medical students often encounter challenges in maintaining healthy habits. The Preventive Remediation for Optimal MEdical StudentS (PROMESS) project seeks to support students to adopt healthier lifestyles throughout their curriculum by implementing a program focused on three modules (stress, sleep, and physical activity). Prior to implementation, it was essential to gain insights into students' needs. For this purpose, a comprehensive approach was adopted to ensure that the proposed program aligns with students’ needs, to identify barriers and facilitators for implementation, to propose adjustments, and to test the program. Methods A three-step study was conducted. First, two focus groups sessions, one involving students and the other involving university staff members were conducted to identify medical students' needs and obstacles to change regarding their health. After verbatim transcription, a framework thematic analysis was performed with the use of MAXQDA. Second, a co-construction workshop was conducted with participants from both groups to develop the PROMESS program. Third, some of the medical students who participated in the prior steps tested the co-constructed program. The study was conducted at the Lyon-Est Faculty of Medicine (France, IRB2023070404). Results (i) The medical students cited a heavy academic workload and demanding internships as the main factors that contribute to their limited selfcare, heightened stress levels and sleep disruptions, and reduced physical activity. The university staff members noted that students struggled to acknowledge their needs, accept limitations, and seek assistance. (ii) The participants provided advice for adapting PROMESS program to the students’ specific needs (e.g., individualized advice, one-on-one meetings, peer coaching, and signing a commitment contract). (iii) The students who tested the program reported being more aware of their health behaviors and reported improvement in stress levels, sleep, and physical activity. They believed that the changes could be long-lasting. Conclusion This study identified barriers to changes in medical students’ behaviors that affect their health. The co-construction workshop and the pilot study facilitated program development and enhanced its feasibility and acceptability for broader implementation. This three-step approach highlights the importance of engaging various stakeholders to craft complex health interventions for medical students.